An examination of neurocognition and symptoms as predictors of post-hospital community tenure in treatment resistant schizophrenia. (28th February 2016) - Ahmed, Anthony O.; Murphy, Christopher F.; Latoussakis, Vassilios; McGovern, Kelly E.; English, Judith; Bloch, Andrew; Anthony, Donna T.; Savitz, Adam J.
Abstract: Neurocognition and psychopathology are robust predictors of community functioning and relapse/rehospitalization in schizophrenia. Existing studies are however limited because they have ignored the most chronic, treatment-resistant patients. Moreover, the prediction of functional outcomes has yet to be extended to the duration of community tenure, an indicator of the capacity of chronically-hospitalized patients to gain traction in the community. The current study examined neurocognition and symptom severity at discharge as potential predictors of community tenure in chronically-hospitalized treatment-resistant patients. The study recruited 90 people with treatment-resistant schizophrenia who received services on an inpatient unit. Participants completed measures of psychopathology and neurocognition prior to discharge. Following discharge, participants were tracked at current residences six months and one year post-discharge to assess community tenure. The percentage of individuals who continued to live in the community at 12-month follow-up was 51%. Severe negative symptoms but not neurocognitive impairment or positive symptoms was a significant predictor of shorter post-hospital community tenure. Of the negative symptoms domain, anhedonia-asociality proved to be the most relevant predictor of community tenure in the sample. The capacity to elicit goal-directed behaviors in response to anticipated physical and social rewards may be an important treatment target for sustaining community tenure. Highlights: We evaluated neurocognition and symptoms as predictors of community tenure in schizophrenia. Lower levels of anhedonia/asociality predicted community survival at 1-year follow-up. Positive symptoms and neurocognitive impairment did not predict community tenure.